Role of Social, Economic, Environmental, Psychological, Educational factors, Ayurveda on Food Habits in our Day-to Day Life (International Journal of Food and Nutritional Sciences, 2022)
Our current paper aim is to aware one and all about the general food habits includes what to eat and what not to eat. Our work also reveals about the study of different factors like Social, Economic, Environmental, Psychological, Educational, Media factors which affects our Food Habits in our Day-to Day Life. This paper is the voice of people and shouting out about the need to improvement in people's food choices, need to aware about the barriers to dietary change, which vary with life stages, need of attention about major challenge both to health professionals and to the public themselves to effect dietary change. This paper also tries to introduce an understanding that Human body is a bio-product of food. Healthy life goes with healthy food. Food is a medicine and food play’s an important role in healthy, & diseased condition. Our efforts in this paper reflects that the strength and complexion of an individual will enhance only if we all follows correct diet and regimen.